WWOX-related epileptic encephalopathy caused by a novel mutation in the WWOX gene: a case report - Feng, Dan; Li, Ye; Zhang, Ya-Ting; Song, Yan-Jun; Qin, Dong-Yuan; Wang, Fan (Frontiers in Pediatrics, 2024)
Background WWOX-related epileptic encephalopathy is an autosomal recessive disorder caused by mutations in the WW-containing oxidoreductase gene, characterized by the onset of refractory seizures in infants. Early-onset epilepsy, electroencephalography abnormalities, and developmental delay or degeneration are the main clinical manifestations. Early death can occur in severe cases. In the present study, a novel variant in WWOX was detected in a patient with epilepsy and his healthy parents. Case presentation A 5-month-old boy presented with epilepsy. The main manifestations were intractable seizures, mental and motor retardation and hearing impairment. Subsequent genetic testing revealed the presence of an epilepsy-associated novel mutation: c.991C>A (amino acid change: p.Ser304Tyr) in the WWOX gene. Variants were inherited from parents with healthy phenotypes. Finally, a patient died at 6 months of age. Conclusion The discovery of novel variants has enriched the existing database of WWOX gene variants and may expand the range of clinical options for treating WWOX-related disorders.